Heteroepitaxial Growth of B5‐Site‐Rich Ru Nanoparticles Guided by Hexagonal Boron Nitride for Low‐Temperature Ammonia Dehydrogenation. Issue 4 (11th August 2022) - Kang, Sungsu; Cha, Junyoung; Jo, Young Suk; Lee, Yu‐Jin; Sohn, Hyuntae; Kim, Younhwa; Song, Chyan Kyung; Kim, Yongmin; Lim, Dong‐Hee; Park, Jungwon; Yoon, Chang Won
Abstract: Ruthenium is one of the most active catalysts for ammonia dehydrogenation and is essential for the use of ammonia as a hydrogen storage material. The B5 ‐type site on the surface of ruthenium is expected to exhibit the highest catalytic activity for ammonia dehydrogenation, but the number of these sites is typically low. Here, a B5 ‐site‐rich ruthenium catalyst is synthesized by exploiting the crystal symmetry of a hexagonal boron nitride support. In the prepared ruthenium catalyst, ruthenium nanoparticles are formed epitaxially on hexagonal boron nitride sheets with hexagonal planar morphologies, in which the B5 sites predominate along the nanoparticle edges. By activating the catalyst under the reaction condition, the population of B5 sites further increases as the facets of the ruthenium nanoparticles develop. The electron density of the Ru nanoparticles also increases during catalyst activation. The synthesized catalyst shows superior catalytic activity for ammonia dehydrogenation compared to previously reported catalysts. This work demonstrates that morphology control of a catalyst via support‐driven heteroepitaxy can be exploited for synthesizing highly active heterogeneous catalysts with tailored atomic structures. Abstract : A highly active Ru catalyst with abundant active sites for ammonia dehydrogenation, which is essential for utilizing ammonia as a hydrogen carrier, is prepared by a novel synthesis method. A highly active Ru catalyst with a unique atomic structure is designed to induce the formation of hexagonal planar‐shaped Ru nanoparticles with abundant B5 sites by utilizing 2D hexagonal boron nitride as a template support.